2015
DOI: 10.1080/10408398.2015.1045967
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical-mediated Protein Expression Profiling and the Potential Applications in Therapeutic Drug Target Identifications

Abstract: Many phytochemicals derived from edible medicinal plants have been investigated intensively for their various bioactivities. However, the detailed mechanism and their corresponding molecular targets frequently remain elusive. In this review, we present a summary of the research works done on phytochemical-mediated molecular targets, identified via proteomic approach. Concurrently, we also highlighted some pharmaceutical drugs which could be traced back to their origins in phytochemicals. For ease of presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Numerous studies have previously reported on how plant phytochencal contents are directly linked to their bioactivities and pharmacological potentials ( Cao et al, 2017 , Teng et al, 2019 , Wong et al, 2016 ). In order to determine the effect of protein hydrolysate (PH) treatments, the harvested hydroponic lettuce samples were firstly tested for the phytochemical contents in three categories, namely total phenolic content (TPC), total flavonoid content (TPC), and total hydroxycinnamic acid content (THC).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have previously reported on how plant phytochencal contents are directly linked to their bioactivities and pharmacological potentials ( Cao et al, 2017 , Teng et al, 2019 , Wong et al, 2016 ). In order to determine the effect of protein hydrolysate (PH) treatments, the harvested hydroponic lettuce samples were firstly tested for the phytochemical contents in three categories, namely total phenolic content (TPC), total flavonoid content (TPC), and total hydroxycinnamic acid content (THC).…”
Section: Resultsmentioning
confidence: 99%
“…58 These combinatorial studies could provide opportunities for phytochemicals to be developed into site-and targetspecific anticancer agents. 59…”
Section: Phytochemical Mediated Differential Expression Of Protein Targetsmentioning
confidence: 99%
“…The most successful discoveries are the vinca alkaloids (vinblastin and vincristine) from Catharanthus roseus. 23…”
Section: Breastmentioning
confidence: 99%
“…58 These combinatorial studies could provide opportunities for phytochemicals to be developed into site-and targetspecific anticancer agents. 59 Nano formulations for optimal activity 62 miRNAs are involved in all stages of colorectal cancer. 63 Curcumin, resveratrol, quercetin, alpha-mangostin, Vitamin D, omega-3 PUFA have been reported with miRNA modulatory activity.…”
Section: Phytochemical Mediated Differential Expression Of Protein Tamentioning
confidence: 99%